Pituitary Gland and Neurological Involvement in a Case of Hemophagocytic Syndrome Revealing an Intravascular Large B-Cell Lymphoma - Sylvain Raoul Simeni Njonnou; Bruno Couturier; Yannick Gombeir; Sylvain Verbanck; France Devuyst; Georges El Hachem; Ivan Theate; Anne-Laure Trepant; Virginie De Wilde; Frédéric-Alain Vandergheynst (Case Reports in Hematology)
Intravascular large B-cell lymphoma is a rare entity characterized by the proliferation of neoplastic lymphocytes in the lumen of small blood vessels and high mortality. Diagnosis of intravascular lymphoma is often delayed or established postmortem. Here, we report the case of a 48-year-old woman presenting hemophagocytic syndrome, with pituitary gland and neurological involvement. Diagnosis of intravascular large B-cell lymphoma was made on perisplenic vessels, while liver and bone marrow biopsy was noncontributive. This case demonstrates the importance of thorough histopathologic investigations in the setting of high suspicion.